2002
DOI: 10.1016/s0965-1748(01)00122-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel sodium channel gene mutations in Blattella germanica reduce the sensitivity of expressed channels to deltamethrin

Abstract: Pyrethroid insecticides alter the normal gating of voltage-gated sodium channels in the nervous system. Three sodium channel mutations (E434K, C764R, L993F) were recently identified in pyrethroid resistant German cockroach populations. In this report, we show that the L993F mutation decreased sodium channel sensitivity to the pyrethroid, deltamethrin, by five-fold in Xenopus oocytes. In contrast, neither E434K nor C764R alone decreased channel sensitivity to deltamethrin. However, E434K or C764R combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 35 publications
1
104
0
2
Order By: Relevance
“…Assays with channels containing the M827I and L932I mutations, either singly or in combination, also exhibited acceleration of the rate of tail current decay that was correlated with the degree of resistance afforded to 200 μM permethrin. Both the reduction in permethrin sensitivity and the acceleration of tail current decay observed with channels containing the M827I and L932I mutations are qualitatively similar the to the previously-characterized effects of the V410M and L1014F mutations on the permethrin sensitivity of D. melanogaster Para/tipE sodium channels (Lee et al, 2000a;Feng et al, 1995;Smith et al, 1997;Warmke et al, 1997;Tan et al, 2002b;Smith et al, 1998;Zhao et al, 2000;Vais et al, 2000;Lee et al, 1999b) and the cismethrin sensitivity of Vssc1 WT /tipE sodium channels (Lee et al, 2000a;Feng et al, 1995;Smith et al, 1997;Warmke et al, 1997;Tan et al, 2002b;Smith et al, 1998;Zhao et al, 2000;Vais et al, 2000;Lee et al, 1999b).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Assays with channels containing the M827I and L932I mutations, either singly or in combination, also exhibited acceleration of the rate of tail current decay that was correlated with the degree of resistance afforded to 200 μM permethrin. Both the reduction in permethrin sensitivity and the acceleration of tail current decay observed with channels containing the M827I and L932I mutations are qualitatively similar the to the previously-characterized effects of the V410M and L1014F mutations on the permethrin sensitivity of D. melanogaster Para/tipE sodium channels (Lee et al, 2000a;Feng et al, 1995;Smith et al, 1997;Warmke et al, 1997;Tan et al, 2002b;Smith et al, 1998;Zhao et al, 2000;Vais et al, 2000;Lee et al, 1999b) and the cismethrin sensitivity of Vssc1 WT /tipE sodium channels (Lee et al, 2000a;Feng et al, 1995;Smith et al, 1997;Warmke et al, 1997;Tan et al, 2002b;Smith et al, 1998;Zhao et al, 2000;Vais et al, 2000;Lee et al, 1999b).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, cypermethrin causes profound use-dependent modification of sodium currents with more persistent tail currents than those induced by cismethrin (Smith et al, 1998;Lee et al, 1999b). Studies with deltamethrin, a close structural relative of cypermethrin, and other insect sodium channels in the Xenopus oocyte expression system confirm the exclusively use-dependent action of these α-cyano pyrethroids (Vais et al, 2000;Tan et al, 2002b;Vais et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Up to date, the full length cDNA clones for only 3 orthologous para genes have been identified: in the housefly Musca domestica (Vssc1), the German cockroach Blattella germanica (BgNa V ) and the mite Varroa destructor (VmNa V ) (Dong, 1997;Ingles et al, 1996;Wang et al, 2003). All 3 genes generate voltage-dependent sodium currents when heterologously expressed in oocytes (Du et al, 2009;Ingles et al, 1996;Tan et al, 2002b). A functional characterization of 20 BgNa V splice variants demonstrated that, similar to para, RNA editing and alternative splicing results in an astonishing diversity of Na V channels with distinct expression levels and varying kinetics of gating.…”
Section: Structural Comparison Between Mammalian and Insect Na V Chanmentioning
confidence: 99%